The importance of time perspective in media multitasking behavior - Rogojina, Alena A.; Kantner, Justin; Gentile, Douglas A. (Frontiers in Psychology, 2025)
IntroductionMedia multitasking (using several forms of media at once or using media during a non-media activity) occurs frequently in daily life, though some multitask more than others. This study investigated how individual differences in tendency toward immediate gratification, conceptualized using dual-process and dual-motive models of self-control, are associated with frequency of media multitasking behavior.MethodsThis report extends existing knowledge and offers a comprehensive view by combining self-report survey measures with objective behavioral tasks in two U. S. student samples (Study 1 from a Hispanic-Serving Institution, N = 487; and Study 2 from a Midwestern research university, N = 381). Participants completed self-report measures of media multitasking frequency, effortful control, mindfulness, and time perspective (future versus immediate-goal focus). They also answered retrospective time estimation questions and completed a Time Production (in Study 1 only) and Stop Signal task using E-Prime Go. Individual multitasking scores, media combinations, and in-study multitasking were also examined, and in Study 2 participants also completed a delay discounting measure.ResultsComponents of cognitive control had significant negative associations with media multitasking behavior. The strongest positive associations were with having a present-focused time perspective and favoring immediate over distal rewards. Issues with time estimation played a role as well.DiscussionOverall, our findings suggest that a preference for immediate reward might outweigh cognitive control ability when predicting media multitasking behavior.